2016
DOI: 10.1002/1873-3468.12205
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP2 promotes colorectal cancer cell proliferation and survival through interfering with RAF‐1 degradation by miR‐195

Abstract: Insulin-like growth factor 2 (IGF2) mRNA-binding protein 2 (IGF2BP2) is a post-transcriptional regulatory factor implicated in mRNA localization, stability, and translational control. However, the role of IGF2BP2 regulation in colorectal cancer (CRC) and its underlying mechanism remain elusive. In this study, we found that IGF2BP2 expression is markedly increased in CRC tissues. Notably, IGF2BP2 overexpression strikingly enhanced the proliferation and survival of CRC cells in vitro, whereas its shRNA-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 30 publications
7
72
0
1
Order By: Relevance
“…Based on the GO and KEGG analyses of more than 60 esophageal adenocarcinoma patients, it has been reported that IGF2BP2 is significantly associated with proliferation and growth [10]. In addition, a recent study reported that the knockdown of IGF2BP2 expression in colorectal cancer cells suppressed cell growth [31]. Our results also showed that the knockdown of IGF2BP2 expression in AML cell lines obviously repressed cell growth.…”
Section: Discussionsupporting
confidence: 66%
“…Based on the GO and KEGG analyses of more than 60 esophageal adenocarcinoma patients, it has been reported that IGF2BP2 is significantly associated with proliferation and growth [10]. In addition, a recent study reported that the knockdown of IGF2BP2 expression in colorectal cancer cells suppressed cell growth [31]. Our results also showed that the knockdown of IGF2BP2 expression in AML cell lines obviously repressed cell growth.…”
Section: Discussionsupporting
confidence: 66%
“…IGF2BP2-AS1 is a lncRNA located in the IGF2BP2 antisense strand. IGF2BP2 promotes many cancer types [4042], and IGF2BP2-AS1 might regulate IGF2BP expression, thus suppressing LUSC development and progression. DGCR5 is a DiGeorge syndrome-related gene [43], and its role in cancers is currently uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IGF2BP2 can inhibit the translation of the mitochondrial transport protein, uncoupling protein‐1 (UCP1), a protein which has was shown to bring about autophagy and cell death in a breast cancer model . Elevated levels of IGF2BP2 are also linked to increased rates of metastasis and poor survival in other cancers, including oesophageal and colorectal carcinomas .…”
Section: Identification Of Pro‐oncogenic Factors In 3q26‐29mentioning
confidence: 99%